Endometrial Involvement in Pseudomyxoma Peritonei Secondary to Low-Grade Appendiceal Mucinous Neoplasm. (May 2015) - McVeigh, Gerard; Shah, Varsha; Longacre, Teri A.; McCluggage, W. Glenn
<x xml:space="preserve">Abstract</x> Pseudomyxoma peritonei is a clinical condition characterized by the presence of mucinous ascites, usually with variable amounts of neoplastic enteric-type mucinous epithelium, and most commonly secondary to spread from a low-grade appendiceal mucinous neoplasm. We report 2 cases of pseudomyxoma peritonei associated with low-grade appendiceal mucinous neoplasms where there was colonization of the endometrium (both cases) and cervical mucosa (1 case) by low-grade atypical enteric-type mucinous epithelium (CK20 positive and CK7 negative). The patients had symptoms of mucoid vaginal discharge and endometrial biopsies in both (1 patient had multiple endometrial biopsies over a period of 11 mo) and were initially interpreted as representing mucinous metaplasia. Pseudomyxoma peritonei may rarely result in endometrial and cervical mucosal involvement, presumably secondary to transtubal spread.